Use of a Chemical‐Looping Reaction to Determine the Residence Time Distribution of Solids in a Circulating Fluidized Bed. Issue 10 (21st June 2016) - Donat, Felix; Hu, Wenting; Scott, Stuart A.; Dennis, John S.
Abstract: The residence time distribution (RTD) of solids in various sections of a circulating fluidized bed (CFB) is of great importance for design and operation but is often difficult to determine experimentally. A noninvasive method is described, for which the RTD was derived from temporal measurements of the temperature following the initiation of a chemical‐looping reaction. To demonstrate the method, a CuO‐based oxygen carrier was used in a small‐scale CFB, and measurements were made in the fuel reactor, operated as a bubbling fluidized bed. The measurements were fitted to the tanks‐in‐series model, modified to account for heat losses from the reactor. There was excellent agreement between the model and the experiment. Limitations and further improvements of the method are discussed, also with respect to larger reactors. Abstract : A little loopy : A noninvasive method is used to derive the residence time distribution of solids in a chemical‐looping reactor. For this, a looping reaction is initiated and the increase in temperature is related to a solids mixing model, namely, the tanks‐in‐series model modified for effects of heat transfer.